Mr. Saturday night [compact disc] - Pardi, Jon, 1985- (Capitol Nashville, 2022)
Country music star Jon Pardi channels personal experiences into his fourth studio album, which includes Last Night Lonely; Fill 'Er Up; and the album's title track.